Meyler's side effects of drugs the international encyclopedia of adverse drug reactions and interactions - Aronson, J. K.; Dukes, M. N. G. (Elsevier, 2006)
"This is a completely new edition of what has become the standard reference text in the field of adverse drug reactions and interactions since Leopold Meyler published his first review of the subject 55 years ago. Although we have retained the old title, Meyler's Side Effects of Drugs, the subtitle of this edition, The Encyclopedia of Adverse Drug Reactions and Interactions, reflects both modern terminology and the scope of the review. The structure of the book may have changed, but the Encyclopedia remains the most comprehensive reference source on adverse drug reactions and interactions and a major source of informed discussion about them."
Title from resource title page (Gale Virtual Reference, viewed Dec. 16, 2010).
Keywords: léky; vedlejší účinky léků; farmakologie; drugs; side effects of drugs; pharmacology; encyklopedie; elektronické knihy; encyclopedias; electronic books